(untitled) (Community Based Medical Journal, 2024)
This quasi-experimental study was conducted in the Department of Ophthalmology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, and Bangladesh Eye Hospital, Dhaka, Bangladesh, from March 2020 to August 2021, to compare the efficacy of Bevacizumab and Ranibizumab on patients with choroidal neovascular membrane (CNVM) due to age-related macular degeneration (AMD). A total of 34 eyes of 34 participants with CNVM in AMD divided into Group A, received monthly intravitreal ranibizumab (0.5 mg in 0.05 ml) and Group B, bevacizumab (1.25 mg in 0.05 ml) for 3 consecutive months. Before treatment, mean BCVA was found 37.9412±16.68259 in group A and 35.2941±12.68249 in group B. After treatment, the mean best-corrected visual acuity (BCVA) was found 53.5294±14.97547 in group A and 48.8235±13.75334 in group B. The differences were not statistically significant (p>0.05) between two groups. The improvement in BCVA was highly significant (p<0.0001) in both groups before and after giving intravitreal bevacizumab and ranibizumab. Before treatment, mean central macular thickness (OCT) was found in 344.8824±82.51582 μm in group A and 360.1765±82.22016 μm in group B. After treatment, OCT was found 255.18±71.852 μm in group A and 241.76±42.405 μm in group B. The differences were not statistically significant (p>0.05) between two groups. However, the improvement by decreasing macular thickness was highly significant (p<0.0001) in both groups before and after giving intravitreal bevacizumab and ranibizumab. Treatment with intravitreal bevacizumab or ranibizumab was associated with a similar improvement in mean visual acuity and decreasing central macular thickness by 4 months. CBMJ 2024 July: vol. 13 no. 02 P: 265-273